Caracterização estrutural de duas sulfonamidas e de um análogo de chalcona do tipo retinóide - Fernandes, William Borges (2011)
In order to know the molecular and crystalline structure of chemical compounds for further physical-chemical analysis and application studies, launches hand of crystallography as a scientific methodology that allows to know the structure of any crystalline compound without any a priori information. This methodology is based on concepts such as X-ray diffraction by crystalline materials, symmetry, Bragg's law and Fourier transform. This dissertation presents some fundamental concepts of X-ray crystallography and all the steps of crystallographic methodology. This powerful methodology has been used in the structural elucidation of two organic compounds of aryl-sulphonamide and one retinoidlike analogue of chalcone, both obtained synthetically. The compounds 4-N[(phenyl)- sulphonamideacetophenone] and 4-N[(2,5-dichlorophenyl)-sulphonamideaceto phenone], in which the difference between them is the substitution of two hydrogens at positions 2 and 5 of phenyl ring by chlorine atoms in the (phenyl)benzenesulphonamide molecular framework, were synthesized and characterized by X-ray crystallography. Subsequently was established the influence of the replacement of two chlorine atoms on the conformation and crystal assembly of these two compounds. The other compound synthesized and characterized by X-ray crystallography, was the (1E,4E)-1-(4- nitrophenyl)-5-(2,6,6-trimetylciclohexenyl-1-)-penta-1,4-dien-3-one, that presented a static disorder during the refinement, confirmed after a new data collect at low temperature. This dissertation also presents the modeling of this disorder, and all the analysis of crystallographic data obtained, the molecular geometries and the and the contribution of intermolecular interactions in the crystal packing of the compounds. The results of other complementary methods for structural elucidation, are also presented.